Nonverbal Communication 2013
DOI: 10.1515/9783110238150.613
|View full text |Cite
|
Sign up to set email alerts
|

20 Power, dominance, and persuasion

Abstract: "When two persons interact, they continually negotiate two major relationship issues: how friendly or hostile they will be with each other, and how much in charge or control each will be during their transactions" (Kiesler and Auerbach 2003: 1712). Social interactions can be mapped onto two main dimensions that are perpendicular to each other: the affiliation dimension -also called the horizontal dimension (Hall, Coats, and Smith LeBeau 2005), which is characterized by friendliness and warmth on the one end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Expansiveness signals who is in charge and emphasizes the vertical dimension of relationships (Henley, 1995). In line with this reasoning, power poses are typically described in terms of dominance (e.g., Chadwick, Metzler, Tijus, Armony, & Grèzes, 2019; Holland, Wolf, Looser, & Cuddy, 2017; Park, Streamer, Huang, & Galinsky, 2013) and can be understood as expressions of power or its pursuit (Schmid Mast & Cousin, 2013). To deduce beliefs about the nonverbal expression of power, Carney, Hall, and LeBeau (2005) in fact asked participants to imagine individuals who differed, inter alia, in their trait dominance.…”
Section: Terminology and Theorizingmentioning
confidence: 99%
“…Expansiveness signals who is in charge and emphasizes the vertical dimension of relationships (Henley, 1995). In line with this reasoning, power poses are typically described in terms of dominance (e.g., Chadwick, Metzler, Tijus, Armony, & Grèzes, 2019; Holland, Wolf, Looser, & Cuddy, 2017; Park, Streamer, Huang, & Galinsky, 2013) and can be understood as expressions of power or its pursuit (Schmid Mast & Cousin, 2013). To deduce beliefs about the nonverbal expression of power, Carney, Hall, and LeBeau (2005) in fact asked participants to imagine individuals who differed, inter alia, in their trait dominance.…”
Section: Terminology and Theorizingmentioning
confidence: 99%
“…Dominance can be displayed through postural expansion (vs. constriction; Tiedens & Fragale, 2003); it is a behavioral tendency or pattern of interaction, while relative power is an affordance of the situation. Further, scholars have shown that power and dominance have divergent effects (e.g., Gilad & Maniaci, 2022; Goodwin et al, 1998; Mast & Cousin, 2013) and “should not be equated” (Gilad & Maniaci, 2022, p. 1).…”
Section: Power and Trustmentioning
confidence: 99%
“…The latter aspect of mastery is in focus in the present study, and it refers to an observer's perceptions of the extent to which a specific individual is influential in bringing about desired outcomes in an interaction with another individual. In general, we humans are good at accurately judging signs of power in others; many non-verbal behaviors provide information about this, such as the direction of gaze, nodding, touching each other, and loudness of speech (Schmid Mast and Cousin, 2013). In addition, it is assumed that obedience and disobedience in human-to-human interactions provide archetypical cues about an individual's mastery, so the observer who watches an order giver being obeyed in a social setting is expected to ascribe a higher level mastery to this order giver compared to an order giver who is disobeyed.…”
Section: Obedience and Masterymentioning
confidence: 99%